2020
DOI: 10.1016/j.jseint.2020.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Do glenoid retroversion and humeral subluxation affect outcomes following total shoulder arthroplasty?

Abstract: Background Glenoid retroversion and humeral head subluxation have been suggested to lead to inferior outcomes after total shoulder arthroplasty (TSA). There are limited data to support this suggestion. We investigated whether preoperative glenoid retroversion and humeral head subluxation are associated with inferior outcomes after TSA and whether change of retroversion influences outcomes after TSA. Methods Patients undergoing TSA with minimum 2-year follow-up were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In patients with rotator cuff dysfunction, PD can occur as a pre-stage pathology as a result of a similar mechanism to that of posterior HH subluxation in degenerative disease. Although posterior HH subluxation in degenerative disease is currently described as a percentage change from the midline of the scapula [ 22 , 23 ], PD in RCTs is a subtle change. Therefore, we defined PD as a greater than 2 mm posterior shift of the HH to the scapula, based on past studies [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with rotator cuff dysfunction, PD can occur as a pre-stage pathology as a result of a similar mechanism to that of posterior HH subluxation in degenerative disease. Although posterior HH subluxation in degenerative disease is currently described as a percentage change from the midline of the scapula [ 22 , 23 ], PD in RCTs is a subtle change. Therefore, we defined PD as a greater than 2 mm posterior shift of the HH to the scapula, based on past studies [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gregory et al confirmed that an inferiorly inclined glenoid component was associated with increased radiolucent lines [1]. Other research has shown no association between glenoid component version and clinical outcome scores [8,9]. For these reasons, it is important to examine and quantify the glenoid component position over time, and further, to determine whether glenoid component position impacts clinical or patient-reported outcomes.…”
Section: Introductionmentioning
confidence: 99%